N6-Methyladenosine Induced miR-34a-5p Promotes TNF-α-Induced Nucleus Pulposus Cell Senescence by Targeting SIRT1 - Zhu, Hao; Sun, Bao; Zhu, Liang; Zou, Guoyou; Shen, Qiang (Frontiers in Cell and Developmental Biology, 2021)
Low back pain is tightly associated with intervertebral disc degeneration (IVDD) and aberrant nucleus pulposus (NP) is a critical cause. miRNAs N6-methyladenosine (m6A) modification accounts for the TNF-α-induced senescence of NP cells. The aim of this study was to investigate whether m6A modification regulates TNF-α-mediated cell viability, cell cycle arrest, and cell senescence and how it works. The results showed that METTL14 expression positively correlated with m6A and TNF-α expression in HNPCs. The knockdown of METTL14 led to the inhibition of the TNF-α-induced cell senescence. METTL14 overexpression promoted cell senescence. METTL14 regulated the m6A modification of miR-34a-5p and interacted with DGCR8 to process miR-34a-5p. The miR-34a-5p inhibitor inhibited the cell cycle senescence of HNPCs. miR-34a-5p was predicted to interact with the SIRT1 mRNA. SIRT1 overexpression counteracted the miR-34a-5p-promoted cell senescence. METTL14 participates in the TNF-α-induced m6A modification of miR-34a-5p to promote cell senescence in HNPCs and NP cells of IVDD patients. Downregulation of either METTL14 expression or miR-34a-5p leads to the inhibition of cell cycle arrest and senescence. SIRT1 mRNA is an effective binding target of miR-34a-5p, and SIRT1 overexpression mitigates the cell cycle arrest and senescence caused by miR-34a-5p.